Passive and Active Microwave Remote Sensing and Modeling of Layered Snow ... - Fuller, Mark Christopher (Graduate Studies, 2015)
This thesis investigates the effects of complexly-layered snow on passive and active microwave remote sensing observations and models, employing detailed in-situ geophysical measurements over various landcover types. First, I present observed and simulated C-band backscatter signatures for complexly-layered snow on smooth, landfast first-year sea ice. Detailed in-situ measurements describe snow structure. A multilayer backscatter model is used to assess the impacts of layered components. The backscatter from a complexly-layered snow cover on smooth first-year sea ice is higher than from a simple snow cover. Sensitivity analysis suggests that rough ice layers within the snow cover and superimposed at the snow-ice interface influence brine volume, and are mechanisms that increase surface and volume scattering. This has implications for sea ice mapping, geophysical inversion, and snow thickness retrievals. Second, I present a snow layer excavation experiment to compare observed and modeled brightness ...